2020
DOI: 10.3389/fpls.2020.00654
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Composition of Agave americana L. Yields Greater Carbohydrates From Enzymatic Hydrolysis Than Advanced Bioenergy Crops

Abstract: Agave americana L. is a highly productive, drought-tolerant species being investigated as a feedstock for biofuel production. Some Agave spp. yield crop biomass in semi-arid conditions that are comparable to C 3 and C 4 crops grown in areas with high rainfall. This study evaluates the bioethanol yield potential of A. americana by (1) examining the relationship between water use efficiency (WUE) and plant carbohydrates, (2) quantifying the carbohydrate and energy content of the plant tissue, and (3) comparing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 87 publications
1
11
1
Order By: Relevance
“…in the United States under three different levels of water input. Modeling studies have shown that O. ficus‐indica exhibits higher CO 2 uptake potential across a wider range of maximal daytime temperatures (Owen & Griffiths, 2014) and greater resilience to climate change than Agave tequilana and related Agave spp., which are used for beverage production and show great potential as emerging bioenergy and biomaterials crops (Corbin et al, 2015; Escamilla‐Treviño, 2012; Holtum et al, 2011; Jones et al, 2020; Li et al, 2014; Owen et al, 2016; Yan et al, 2011). Modeling projections for O. ficus‐indica production in Australia (Owen & Griffiths, 2014), North America (Yang et al, 2015), and globally, estimated a maximal productivity of up to 40 Mg DM ha −1 (Owen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in the United States under three different levels of water input. Modeling studies have shown that O. ficus‐indica exhibits higher CO 2 uptake potential across a wider range of maximal daytime temperatures (Owen & Griffiths, 2014) and greater resilience to climate change than Agave tequilana and related Agave spp., which are used for beverage production and show great potential as emerging bioenergy and biomaterials crops (Corbin et al, 2015; Escamilla‐Treviño, 2012; Holtum et al, 2011; Jones et al, 2020; Li et al, 2014; Owen et al, 2016; Yan et al, 2011). Modeling projections for O. ficus‐indica production in Australia (Owen & Griffiths, 2014), North America (Yang et al, 2015), and globally, estimated a maximal productivity of up to 40 Mg DM ha −1 (Owen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…was suitable for agricultural production in the southwestern USA with significant differences in the response to different water inputs emerging in years 4 and 5 of the study. After 3 years, annual dry matter biomass production rates at comparable planting densities exceeded those observed for Agave americana , a high‐yielding commercial CAM crop (Davis et al, 2017; Jones et al, 2020).…”
Section: Introductionmentioning
confidence: 88%
“…Goycoolea and Cárdenas, 2003 ; Ginestra et al , 2009 ), and Agave (e.g. Li et al , 2014 ; Jones et al , 2020 ). The interest in Aloe vera (L.) Burm.f.…”
Section: Cell Walls Of Succulent Tissues Under Droughtmentioning
confidence: 99%
“…The recalcitrance of A. americana was compared with sorghum, switchgrass and miscanthus. Authors reported that A. americana is more easily hydrolyzed by enzymes with greater sugar yield per unit mass [95] and can produce substantial yields of soluble carbohydrates with lower amount of enzymes with the same polysaccharides depolymerization to fermentable monosaccharides than other lignocellulosic feedstocks.…”
Section: Biofuels Bioenergy and Byproducts From Agave Speciesmentioning
confidence: 99%